2017
DOI: 10.1177/2050312117741823
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery anomalies: Unusually high incidence of anomalies with a malignant course in an Asian population

Abstract: Objectives:Coronary artery anomalies are uncommon, but important cardiac malformations, representing the second commonest cause of death in young athletes.Methods:We utilized computerized tomographic angiography to screen and precisely delineate coronary artery anomalies in patients with minimal cardiac symptoms.Results:During 3.5-year period, we performed 2888 computerized tomographic angiographies. A total of 33 (1.1%; 95% confidence interval = 0.7–1.5) cases of coronary artery anomalies were identified (mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 12 publications
2
5
0
Order By: Relevance
“…Malignant course of the anomalous coronary artery located inbetween the aorta and the pulmonary arterial trunk with an increased risk for sudden death. The current study showed an incidence of this anomaly in 0.9% of the studied patients, this was in line with Alkhulaifi et al, 2017 [13] who reported nearly the same percentage (0.8%). In the current study, one case was reported with RCA splittage into two arteries just after originating from its ostium in the right sinus of Valsalva (0.1%) and this is similar to the results of a study of Kosar et al, 2009 [14].…”
Section: Discussionsupporting
confidence: 93%
“…Malignant course of the anomalous coronary artery located inbetween the aorta and the pulmonary arterial trunk with an increased risk for sudden death. The current study showed an incidence of this anomaly in 0.9% of the studied patients, this was in line with Alkhulaifi et al, 2017 [13] who reported nearly the same percentage (0.8%). In the current study, one case was reported with RCA splittage into two arteries just after originating from its ostium in the right sinus of Valsalva (0.1%) and this is similar to the results of a study of Kosar et al, 2009 [14].…”
Section: Discussionsupporting
confidence: 93%
“…Despite this extremely high feasibility, the detection rate of AAOCA by echocardiography seems to be suboptimal. Indeed, the known estimates of AAOCA by CCTA, CMR, and autoptic studies range from 0.3% to 1.8% [ 4 , 7 , 23 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ], while echocardiographic studies reported significant lower incidences, ranging from 0% [ 15 , 24 , 30 ] to 0.09% [ 20 ] and up to 0.76% [ 23 ]. However, echocardiographic studies with low incidences of AAOCAs were either retrospective [ 15 ] or used echocardiography in a fast-echo approach in the context of preparticipation evaluation of athletes [ 24 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the interest in the noninvasive evaluation of anomalous aortic origin of coronary arteries (AAOCA) has increased and multiple imaging, surgical and autoptic studies have been published [ 1 , 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. AAOCAs are rare defects with estimates varying from 0.2% to 2.2% in autopsy series [ 23 ] and from 0.3% to 1.8% in Coronary Computed Tomography Angiography (CCTA) studies [ 4 , 7 , 24 ]. Despite being rare, AAOCAs have been recognized as important lesions with significant potential morbidity and mortality, since they represent the second cause of sudden cardiac death (SCD) in athletes [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alkhulaifi et al reported that Asian and Middle Eastern population have a relatively higher incidence of malignant CAA, with passage of the major aberrant trunk between the two great vessels [ 33 ]. This could be explained by higher relative marriage in these countries which facilitates the transmission of any genetic or genetic-related disorder.…”
Section: Discussionmentioning
confidence: 99%